LDL-cholesterol lowering and renal outcomes. Issue 3 (June 2015) - Waters, David D.
<x xml:space="preserve">Abstract</x> Purpose of review Patients with chronic kidney disease (CKD) are at high risk for cardiovascular events. Statins reduce cardiovascular risk in a broad spectrum of patients. This article summarizes the evidence that statins reduce risk in CKD patients, and that statins have a small but favorable effect on renal function. Current guidelines for lipid management in patients with CKD are also reviewed. Recent findings Two well conducted randomized trials showed no significant benefit for statins among patients receiving dialysis. One large trial demonstrated that simvastatin/ezetimibe reduced cardiovascular events in a broad spectrum of CKD patients. A recent meta-analysis concluded that CKD patients benefit from statins, and that the relative benefit decreases as the severity of CKD worsens. In large trials, statin-treated patients have slightly less worsening of renal function overtime, and there are data to suggest that statins actually do not only preserve, but also increase renal function. Recent guidelines recommend a statin for CKD patients aged 50 years or older, for younger patients with known vascular disease, diabetes, or a 10-year risk greater than 10%, and for adult renal transplant recipients. Summary Statins should be prescribed to older patients with CKD, and to younger patients with CKD who are at high CVD risk.